Werturteilsfreiheit? Approach to the ethical “bounds” of modern science - Fonti, Diego Osvaldo (2011)
What can scientific knowledge mean for our moral life, especially if we focus our attention at the level of those value-judgments habitually bound to the results of the scientific quest? Is there any connection between the endlessness of the scientific questioning of the world and the infinity of those in front of whom we pose that question? These questions bring to mind an influential author of the 20th century: Emmanuel Levinas. His first main work is called Totality and Infinity. An Essay on Exteriority, and his whole point is to show that when meeting another human being, when really seeing his countenance, his face, a meaning is shown, that exceeds and surpasses every power of reason, every concept, every institution and every scientific result – in philosophical terms every “totality” –, because in the concrete face of the Other an Infinity is shown and calls us in the shape of a commandment. And the only genuine answer is the responsibility for his or her life. But how could we argue from this “radical experience” of the Other and forge a bridge towards the results – knowledge and technical power – of science?